LRPPRC mutations cause a phenotypically distinct form of Leigh syndrome with cytochrome c oxidase deficiency. Issue 3 (25th January 2011) - Debray, François-Guillaume; Morin, Charles; Janvier, Annie; Villeneuve, Josée; Maranda, Bruno; Laframboise, Rachel; Lacroix, Jacques; Decarie, Jean-Claude; Robitaille, Yves; Lambert, Marie; Robinson, Brian H; Mitchell, Grant A
Abstract : Background: The natural history of all known patients with French-Canadian Leigh disease (Saguenay-Lac-St-Jean cytochrome c oxidase deficiency, MIM220111, SLSJ-COX), the largest known cohort of patients with a genetically homogeneous, nuclear encoded congenital lactic acidosis, was studied. Results: 55 of 56 patients were homozygous for the A354V mutation in LRPPRC . One was a genetic compound (A354V/C1277Xdel8). Clinical features included developmental delay, failure to thrive, characteristic facial appearance and, in 90% of patients, acute crises that have not previously been detailed, either metabolic (fulminant lactic acidosis) and/or neurological (Leigh syndrome and/or stroke-like episodes). Survival ranged from 5 days to >30 years. 46/56 patients (82%) died, at a median age of 1.6 years. Of 73 crises, 38 (52%) were fatal. The immediate causes of death were multiple organ failure and/or Leigh disease. Major predictors of mortality during crises (p<0.005) were hyperglycaemia, hepatic cytolysis, and altered consciousness at admission. Compared to a group of SURF1-deficient Leigh syndrome patients assembled from the literature, SLSJ-COX is distinct by the occurrence of metabolic crises, leading to earlier and higher mortality (p=0.001). Conclusion: SLSJ-COX is clinically distinct, with acute fatal acidotic crises on a backdrop of chronic moderate developmental delay and hyperlactataemia. Leigh syndrome is common. Stroke-like episodes can occur. The Leigh syndrome of SLSJ-COX differs from that of SURF1-related COX deficiency. SLSJ-COX has a different spectrum of associated abnormalities, acidotic crises being particularly suggestive of LRPPRC related Leigh syndrome. Even among A354V homozygotes, pronounced differences in survival and severity occur, showing that other genetic and/or environmental factors can influence outcome.